2013
DOI: 10.2174/18715206113139990136
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Activation Enhances the Anti-proliferative Effect of Paclitaxel in Murine Breast Tumor Cells

Abstract: Muscarinic acetylcholine receptors (mAChR) are expressed in cells without nervous origin. mAChR are up-regulated in tumor cells and their stimulation can modulate tumor growth. In this work we investigated the ability of mAChR activation to induce tumor cell death. We studied the action of a combination of low doses of the muscarinic agonist carbachol plus paclitaxel, a chemotherapeutic agent frequently used in breast cancer treatment, in terms of effectiveness. Long term treatment with carbachol exerted anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…We also observed that the long term addition either of carbachol or APE (non-selective and M 2 receptor selective agonists, respectively) reduced cell viability in these breast tumor cells. Previous results from our group and also from other authors pointed to the ability of these muscarinic agonists to produce cell death in murine breast, bladder and neuronal tumor cells [14-16]. These results let us consider muscarinic receptors as specific therapeutic targets for the treatment of TN breast tumors since they are classified as very aggressive and malignant.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We also observed that the long term addition either of carbachol or APE (non-selective and M 2 receptor selective agonists, respectively) reduced cell viability in these breast tumor cells. Previous results from our group and also from other authors pointed to the ability of these muscarinic agonists to produce cell death in murine breast, bladder and neuronal tumor cells [14-16]. These results let us consider muscarinic receptors as specific therapeutic targets for the treatment of TN breast tumors since they are classified as very aggressive and malignant.…”
Section: Discussionsupporting
confidence: 64%
“…Their role in the regulation of important cell functions like mitosis, cell morphology, locomotion and immune response which are key steps during tumor progression has been documented [12]. The long-term activation of these receptors with the agonist carbachol stimulates cytotoxicity either in human or in murine breast tumor cells [13,14]. In the last years, several reports demonstrated that the activation of M 2 receptor subtype by a selective agonist was able to arrest cell proliferation in different tumor cell lines [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the exposure time and the optimum concentration of paclitaxel for hippocampal neurons were based on a previous study (Español et al. 2012 ). Our results revealed a reciprocal relationship between concentration and exposure time, which is consistent with results of previous studies on paclitaxel in cancer cells (Chirio et al.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the latter, we performed concentration-response and time-response experiments analyzing LM2 and LM 3 cell viability in the presence of carbachol [17]. We observed that carbacholstimulated cell proliferation when it was added to cell cultures for ≤10 h [60,62]. But if cells were treated with the agonist for longer periods of time (≥10 h) it exerted an inhibitory action on tumor cell viability (LM2: 62±6% and LM3: 56±8%) [62].…”
Section: Is It Possible To Target Muscarinic Receptors In Cancer Thermentioning
confidence: 99%